2022
DOI: 10.21037/qims-21-724
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling and subclinical left ventricular dysfunction in adults with uncomplicated obesity: a cardiovascular magnetic resonance study

Abstract: Background: Obesity often exists alongside comorbidities and increases the risk of heart failure and cardiovascular mortality. However, the specific effects of obesity on cardiac structure and function have not been clarified. This study set out to evaluate left ventricular (LV) geometric and functional changes using cardiovascular magnetic resonance imaging (CMR) in adults with uncomplicated obesity.Methods: Forty-eight patients with uncomplicated obesity [body mass index (BMI) mean ± SD: 29.8±2.1 kg/m 2 ] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…Some studies on the correlation between epicardial fat volume (EFV) and CAD reported that the increase of EFV was positively correlated with the risk of CAD [ 16 , 17 ]. Severe CAD often leads to changes in cardiac function, and studies have shown that there is a correlation between EVF and LV function parameters [ 18 , 19 ]. Thus, we analyzed the relationship between PCAT volume, Gensini score, and LV function parameters and found that there was no correlation between them.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the correlation between epicardial fat volume (EFV) and CAD reported that the increase of EFV was positively correlated with the risk of CAD [ 16 , 17 ]. Severe CAD often leads to changes in cardiac function, and studies have shown that there is a correlation between EVF and LV function parameters [ 18 , 19 ]. Thus, we analyzed the relationship between PCAT volume, Gensini score, and LV function parameters and found that there was no correlation between them.…”
Section: Discussionmentioning
confidence: 99%
“…A CMR study conducted by Liu et al demonstrated increased LV size, thickness, and impaired myocardial contractility in Asian patients with uncomplicated obesity with a similar BMI pro le of 28 kg/m 2 . (31) These ndings suggest adverse remodeling starts to occur at lower levels of BMI than previously thought.…”
Section: Discussionmentioning
confidence: 76%
“…We analyzed the relationship between PCAT and CAD, and found that there was no correlation between PCAT volume and Gensini score and cardiac function parameters. However, some studies on the correlation between epicardial fat volume (EFV) and CAD and cardiac function show that the increase of EFV was positively correlated with the risk of CAD and left ventricular function parameters [15][16][17][18] . The possible reason is that the measurement methods are different.…”
Section: Discussionmentioning
confidence: 99%